Can the publication of annual financial reports become an opportunity for insider trading? - Suliga, Milena (Managerial Economics, 2015)
Illegal insider trading is a problem that involves most of financial markets. Unusual abnormal returns as well as increased trading volumes observed ahead o price sensitive information can be signals of this type of market abuse behavior. In this paper, I study the occurrence of insider trading on the Warsaw Stock Exchange. I verify if publications of annual financial reports of WIG issuers can be preceded by this phenomenon. The study includes reports from the period between 1 January, 2010, and 29 May, 2014. In order to define abnormal returns, I suit the GARCH process to daily returns and use event-study analysis. Potential insider trading behaviors are found with the use of two-day cumulative abnormal returns in a first step and with the use of daily abnormal returns afterwards. The publications that are marked with potential informed price movements are analyzed for the presence of extremely high abnormal trading volumes, which can be additional signals of market abuse.